Exploring drivers' mental workload and visual demand while using an in-vehicle HMI for eco-safe driving. (October 2020) - Li, Xiaomeng; Vaezipour, Atiyeh; Rakotonirainy, Andry; Demmel, Sébastien; Oviedo-Trespalacios, Oscar
Highlights: Mental workload and visual demand when using an eco-safe HMI system were studied. Blink variables and pupil size in different eco-safe HMI conditions were analysed. The use of HMI system increased mental workload but within a reasonable level. High visual demand induced by road environment could lead to blink inhibition. Blink measures can be used as valid mental workload and visual demand indicators. Abstract: Eco-safe driving is a promising approach to improve road safety while reducing transport emissions. The application of an eco-safe driving system is feasible with the support of vehicle-to-vehicle/infrastructure technologies. To guarantee system usability and safety appropriateness, a key precondition is to ensure that driver mental workload and visual demands required for using the system are reasonable. This study explored how drivers' mental workload and visual demands were affected when driving with an eco-safe driving HMI (human-machine-interface). Four in-vehicle eco-safe HMI information conditions were evaluated, including baseline, advice only, feedback only, and advice & feedback. Two traffic scenarios (stop-sign intersection with traffic vs. stop-sign intersection without traffic) were simulated using an advanced driving simulator. Behavioural variables (e.g. brake force, acceleration), visual variables (e.g. blink metrics, pupil size) and subjective workload scores were collected from 36 licensed Australian drivers. The experiment results showed that the HMI prompted drivers to apply a smooth and stable brake force when they approached the intersection and a smooth acceleration when they left the intersection. Drivers' mental workload indicated by visual measurements were consistent with their subjective reported workload levels. Drivers had a higher mental workload when they received and processed additional eco-safe information in the advice & feedback condition. An increase in mental workload induced by the in-vehicle cognitive task initiated more blink activities while the increase in visual demand caused by a complex road situation led to blink inhibition. The study shows the HMI could significantly promote eco-safe driving behaivours without causing excessive mental and visual workload of drivers.